Effect of MiR-10b on Cervical Cancer Rats Through mTOR/P70S6K Signaling Pathway: Effect of MiR-10b on Cervical Cancer by mTOR/P70S6K Signaling - Tong, Qiaoling; Hu, Man; Deng, Meixian (Cellular and Molecular Biology, 2022)
The purpose of this experiment was to observe the biological effect and mechanism of miR-10b on cervical cancer (CC) rats. For this purpose, the rat model of CC was established and divided into three groups (Inhibitors/ Mimics/Control). The miR-10b transfection efficiency was analyzed via RT-PCR in cervical tissues in each group. The content of CD3+, CD4+, and CD8+ was detected. The levels of IL-8, TNF-β, IL-6, (CAT, SOD, and MDA were determined via ELISA, and the apoptosis of cervical tissues was detected usingTUNEL assay. The expressions of Caspase-3, Bcl-2, and the mTOR/P70S6K pathway genes and proteins were detected by qRT-PCR and Western blotting. Results showed that miR-10b was significantly increased in the Mimics group and decreased in the Inhibitors group. The content of IL-8, TNF-β, IL-6, CAT and MDA was raised, while that of SOD notably declined in the Inhibitors group. There were remarkably more apoptotic cells in the Mimics group, dominated by gliocytes, and fewer apoptotic cells in the Inhibitors group, with increased content of CD3+, CD4+ and CD8+. The Bcl-2, mTOR, and P70S6K mRNA expressions in the Inhibitors group were up-regulated than those in the other two groups, and the Caspase-3 gene in the Mimics group was increased and close to that in the control group. In the Mimics group, the mTOR and P70S6K protein were remarkably lower than those in the Inhibitors group. In conclusion, miR-10b can inhibit the occurrence and development of CC in rats by suppressing mTOR/P70S6K signaling, reducing the level of inflammation and oxidative stress, and increasing the level of immune factors.